The development of a new multi-faceted model of social wellbeing: Does income level make a difference?. (June 2016) - Povey, Jenny; Boreham, Paul; Tomaszewski, Wojtek
Recent research has suggested that income, while playing a part in quality of life, may have only a limited impact on a multi-faceted concept such as social wellbeing. Using data from an Australian household survey (Living in Queensland Survey), a composite Wellbeing Index was created that covered objective circumstances, with known associations to wellbeing, evaluated from the individual's subjective viewpoint. The importance attributed to each dimension added to the robustness of the measure. The measure was then used to explore the impact of income on wellbeing using various specifications of income. The results indicate that while income is a statistically significant predictor, its effect on wellbeing is small compared with other socio-demographic variables such as health, marital status, employment status and age. The study contributes to the contemporary debate on social wellbeing and adds new evidence to a body of research that has been mainly based on European and American data.